(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
In this paper, an effective formula for the calculation of the elementary functions of a quaternion variable obtained using the methods of differential equations. Also the elementary functions are obtained from the quaternion matrices.